The trends in lung cancer prevalence, incidence, and survival in Hong Kong over the past two decades (2002–2021): a population-based studyResearch in context - Philip CM. Au; Anne WM. Lee; Victor HF. Lee; Ian CK. Wong; Rina YM. Hui; Ching-Lung Cheung (The Lancet Regional Health. Western Pacific, 2024)
Summary: Background: Over the past decades, significant progress in lung cancer management has been made. However, the trends in prevalence and survival of lung cancer in the Chinese population over the last decade remain unexplored. This study utilised a territory-wide electronic medical database in Hong Kong to provide the most up-to-date and comprehensive analysis of the trends in prevalence, incidence, and survival over the past two decades. Methods: Descriptive epidemiology study using a retrospective cohort of lung cancer patients from the Clinical Data Analysis and Reporting System (CDARS). 10-year limited-duration prevalence, incidence, and relative period survival were calculated between 2002 and 2021. Sub-groups of age, sex, and comorbidity were examined. The annual percent change (APC) and average annual percent change (AAPC) were estimated using joinpoint regression. Findings: This study included 87,259 incident cases between 2002 and 2021. The 10-year limited duration prevalence (per 100,000 persons) of lung cancer increased from 153.4 to 228.7 (AAPC: 3.08%). Crude incidence (per 100,000 persons) increased from 55.0 to 70.3 (APC: 1.23%), while age-standardised incidence decreased from 42.9 to 33.2 (APC: −1.32%). The 1-year and 5-year relative period survivals showed an increasing trend but remained low. Disparity in trends was observed among different sex and age groups. Interpretation: Lung cancer burden has been increasing partly due to population ageing. Although survival showed improvement over the years, it remained low, highlighting the potential need for interventions. Further study exploring the disparity in sex-specific trends is warranted. Funding: The Innovation and Technology Commission, Hong Kong.